Spectral signatures of canthaxanthin translocation in the orange carotenoid protein - Pigni, Natalia Belen (2020)
The orange carotenoid protein (OCP) is involved in the photoprotective processes in cyanobacteria via nonphotochemical quenching. Triggered by blue-green light absorption, the carotenoid chromophore undergoes translocation, displacing around 12 Å from the C-terminal domain (CTD) to the N-terminal domain (NTD). The detailed molecular rearrangements that occur within the carotenoid and the protein during this process remain largely elusive. By using a combination of molecular dynamics, well-tempered metadynamics, and hybrid quantum mechanical/molecular mechanical (QM/MM) calculations, we were able to mimic the translocation of the carotenoid from the inactive OCPO and obtain metastable red-shifted states in the photoactivation mechanism, replicating the λmax values of reference experimental spectra. In addition, our simulations give insight into the structure of the red-shifted form of the inactive state of OCP.